More is better … until it is worse: Can organ placement processes scale to an increasingly complex system?. Issue 11 (23rd August 2022) - Adler, Joel T.; Husain, Syed A.
Abstract : The authors comment on Reddy et al's insights (page 2661 ) into a single center's experience with the increased number of organ offers after kidney and liver allocation system changes, emphasizing the increased workload, potential outcomes and possible solutions.